Nosql Technology In Android Based Mobile Chat Application Using Mongodb - Yovita Tunardi; Rita Layona (Bina Nusantara University, 2014)
Along with the development of data storage technology which previously using relational concept began to change to the non-relational concept or sometimes referred to as the term NoSQL technology. Data storage in NoSQL is no longer based on the relations between tables but using another methods, one of them is document-oriented. This method was applied specifically in MongoDB. This concept brings new hope because oftheir superiority that can handle very large data with promising performance and is perfect for agile system development. The purpose of this research was to measure the performance NoSQL, especially MongoDB with implemented it in a Android based mobile chat application. This research uses three methods, analysis method including literature study, analysis of similar application, questionnaires, design method using Agile SofwareDevelopment, and evaluation method including eight golden rules, analysis of similar application, questionnaires, and interview. The results of this research is a mobile chat application that uses MongoDB as the data storage technology. Through this research can be drawn the conclusion that NoSQL technology implementation, MongoDB, give special advantages like lighter data storage and faster data access.